Interfacial Characteristics and Cytocompatibility of Hydraulic Sealer Cements - BENEZRA, MİRA KEBUDİ; BENEZRA, MİRA KEBUDİ; Wismayen, Pierre Schembri; Camilleri, Josette (My University, 2018)
Introduction: The stability and long-term success of root canal obturation depends on the choice of sealer because the sealer bonds to the dentin and stabilizes the solid cone. Furthermore, the sealer needs to be nontoxic because sealer toxicity will certainly lead to treatment failure. The aim of this study was to assess the sealer-dentin interface of 3 hydraulic root canal sealers and to evaluate their cytocompatibility compared with AH Plus (Dentsply DeTrey GmbH, Konstanz, Germany). Methods: Four dental root canal sealers were assessed. AH Plus, MTA Fillapex (Angelus, Londrina, Brazil), BioRoot RCS (Septodont, Saint-Maur-des-Foss4s, France), and Endoseal (Maruchi, Wonju-si, Gangwondo, South Korea) were characterized using scanning electron microscopy and energy-dispersive spectroscopy. The sealer-tooth interface was assessed by confocal microscopy and scanning electron microscopy, and biocompatibility was measured by assessing the cell metabolic function using direct contact assays and alkaline phosphatase activity. Results: The tricalcium silicate based sealers presented a different microstructure and elemental composition despite their similar chemistry and classification. BioRoot RCS was free of aluminum, and all sealers presented different radiopacifying elements. The sealer penetration in the dentinal tubules and interfacial characteristics were different. The migration of silicon was evident from sealer to tooth for all sealers containing tricalcium silicate. MTA Fillapex and BioRoot RCS exhibited the best cytocompatibility in both the direct contact test and alkaline phosphatase activity. Conclusions: The use of hydraulic calcium silicate based sealers has introduced a different material type to endodontics. These materials are different than other sealers mostly because of their hydraulic nature and their interaction with the environment. Although the sealers tested had a similar chemistry, their cytocompatibility and bonding mechanisms were diverse.